2018
DOI: 10.1002/pmh.1437
|View full text |Cite
|
Sign up to set email alerts
|

The Portuguese version of the Personality Inventory for the DSM‐5 in a community and a clinical sample

Abstract: Portuguese version of the Personality Inventory for the DSM-5 in a community and a clinical sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
7
13
0
Order By: Relevance
“…First, there was the issue of irresponsibility facet loading primarily on Psychoticism and only secondarily on Disinhibition, its respective domain. Although there was a relatively small difference between loadings found in this study (λ = 0.37 vs. λ = 0.36), it can be seen as further evidence of proneness of the irresponsibility factor to cross-loadings, previously demonstrated in the extracted PID5BF+M by other studies using the original 220-item version of PID-5 [e.g., (31,32)]. It should be noted that these studies mostly employed samples from the general population or mixed samples with a predominance of respondents from the general population (11).…”
Section: Factor Structure and The Model Fitsupporting
confidence: 61%
“…First, there was the issue of irresponsibility facet loading primarily on Psychoticism and only secondarily on Disinhibition, its respective domain. Although there was a relatively small difference between loadings found in this study (λ = 0.37 vs. λ = 0.36), it can be seen as further evidence of proneness of the irresponsibility factor to cross-loadings, previously demonstrated in the extracted PID5BF+M by other studies using the original 220-item version of PID-5 [e.g., (31,32)]. It should be noted that these studies mostly employed samples from the general population or mixed samples with a predominance of respondents from the general population (11).…”
Section: Factor Structure and The Model Fitsupporting
confidence: 61%
“…Accordingly, in both the Czech sample [31], the US mixed sample [27], and the US student sample [28], distractibility cross-loaded on negative affectivity and psychoticism. Likewise, in the French community sample [34], the Swiss community sample [34], the Portuguese community sample [25], and the Spanish mixed sample [26], irresponsibility primarily loaded negatively on anankastia rather than disinhibition. Moreover, in the Brazilian mixed sample [30] impulsivity cross-loaded on negative affectivity, whereas in the Swiss sample impulsivity cross-loaded on antagonism.…”
Section: Resultsmentioning
confidence: 99%
“…In the present international collaborative study we included a total of 16 samples from different countries, regions, and populations [17, 19, 25-37]. In order to ensure heterogeneity and evade range restriction, we deliberatively incorporated diverse samples including clinical, community, student, and mixed samples.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, although the domain Psychoticism primarily emerged from features of Negative affectivity, Disinhibition, and Detachment [ 53 , 54 ], it has been pointed as heterogeneous, and some studies found deviant facet loading in this domain [ 29 , 55 ]. Others even reported its absence from their factor structure in a clinical sample [ 56 ]. Furthermore, studies that tried to harmonize the DSM-5 trait model with the ICD-11 personality model stated that in order to facilitate the communication between clinicians, the domain Psychoticism should not be conceptualized in terms of personality pathology, as it is considered under the spectrum of schizophrenia disorder by the World Health Organization [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%